Antimicrobial Susceptibility and Genomic Structure of Arcobacter skirrowii Isolates - Hänel, Ingrid; Hotzel, Helmut; Tomaso, Herbert; Busch, Anne (Frontiers in Microbiology, 2018)
Campylobacter spp. are considered the most common foodborne bacterial cause of gastroenteritis in the world. The family Campylobacteraceae includes the genus Arcobacter with the three species, A. butzleri, A. cryaerophilus and A. skirrowii as emergent enteropathogens and potential zoonotic agents. Here, we generated, analyzed and characterized genome sequences of Arcobacter that were isolated from water poultry on farms in Germany. Isolates were cultured, identified by MALDI-TOF MS and identification was verified with PCR. Antibiotic susceptibility testing of isolates was carried out with erythromycin, ciprofloxacin, doxycycline, tetracycline, gentamicin and streptomycin using the gradient strip method (E-test). We also sequenced the whole genomes and predicted antibiotic resistance determinants, virulence factors, plasmids and performed a phylogenetic analysis to determine the genetic relatedness of these isolates.